3D Printing of Hierarchical Porous Ceramics for Thermal Insulation and Evaporative Cooling. Issue 4 (17th October 2022) - Dutto, Alessandro; Zanini, Michele; Jeoffroy, Etienne; Tervoort, Elena; Mhatre, Saurabh A.; Seibold, Zachary B.; Bechthold, Martin; Studart, André R.
Abstract: Materials for thermal management of buildings offer an attractive approach to reduce energy demands and carbon emissions in the infrastructure sector, but many of the state‐of‐the‐art insulators are still expensive, flammable, or difficult to recycle. Here, a 3D printing process is developed and studied to create hierarchical porous ceramics for thermal insulation and passive cooling using recyclable and widely available clay as raw material. Inks comprising particle‐stabilized foams are employed as a template for the generation of the hierarchical porosity. Using foams with optimized rheological properties, the printing parameters and sintering conditions required for the manufacturing of hierarchical porous ceramics via Direct Ink Writing are established. The sintering temperature is found to strongly affect the size distribution of micropores, thus controlling the mechanical, thermal, and evaporative cooling properties of sintered printed structures. By combining suspension‐ and foam‐based inks in a multimaterial printing approach, inexpensive and recyclable clay‐based bricks are manufactured with structural, thermal insulating, and passive cooling capabilities. Abstract : Ceramic porous materials for thermal management offer an attractive approach to reduce energy demands and carbon emissions in the infrastructure sector. 3D printing is a powerful manufacturing technology to create hierarchical porous ceramics for thermal insulation and passive cooling using recyclable and widely available clay as raw material.